Congenital Long QT Syndrome: An Update and Present Perspective in Saudi Arabia - Bhuiyan, M. Z. A.; Al-Shahrani, Safar; Al-Aama, Jumana; Wilde, Arthur; Momenah, Tarek S. (Frontiers in Pediatrics, 2013)
Primary cardiac arrhythmias are often caused by defects, predominantly in the genes responsible for generation of cardiac electrical potential, i.e., cardiac rhythm generation. Due to the variability in underlying genetic defects, type, and location of the mutations and putative modifiers, clinical phenotypes could be moderate to severe, even absent in many individuals. Clinical presentation and severity could be quite variable, syncope, or sudden cardiac death could also be the first and the only manifestation in a patient who had previously no symptoms at all. Despite usual familial occurrence of such cardiac arrhythmias, disease causal genetic defects could also be de novo in significant number of patients. Long QT syndrome (LQTS) is the most eloquently investigated primary cardiac rhythm disorder. A genetic defect can be identified in ∼70% of definitive LQTS patients, followed by Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) and Brugada syndrome (BrS), where a genetic defect is found in <40% cases. In addition to these widely investigated hereditary arrhythmia syndromes, there remain many other relatively less common arrhythmia syndromes, where researchers also have unraveled the genetic etiology, e.g., short QT syndrome (SQTS), sick sinus syndrome (SSS), cardiac conduction defect (CCD), idiopathic ventricular fibrillation (IVF), early repolarization syndrome (ERS). There exist also various other ill-defined primary cardiac rhythm disorders with strong genetic and familial predisposition. In the present review we will focus on the genetic basis of LQTS and its clinical management. We will also discuss the presently available genetic insight in this context from Saudi Arabia.